Identification and Management of Abdominal Wall Varices in Pregnancy. Issue 4 (October 2018) - Wood, Amber M.; Grotegut, Chad A.; Ronald, James; Pabon-Ramos, Waleska; Pedro, Christina; Knechtle, Stuart J.; Wysokinska, Ewa; Rubin, Geoffrey D.; Brady, Carla W.; Gilner, Jennifer B.
Abstract : BACKGROUND: Portal hypertension in pregnancy is associated with elevated risk of variceal hemorrhage. Ectopic varices, those located outside the esophagus or stomach, are rare but have a high risk of associated maternal morbidity or mortality. CASE: A 31-year-old woman, gravida 2 para 0010, with cirrhosis and portal hypertension was found to have abdominal wall ectopic varices on third-trimester obstetric ultrasonography. Computed tomography angiography confirmed these findings. Given concern for catastrophic hemorrhage during delivery, she underwent transjugular intrahepatic portosystemic shunt placement at 35 weeks of gestation, with reduction in the pressure gradient within the portosystemic circulation. She subsequently underwent an uncomplicated cesarean delivery. CONCLUSION: Identification of ectopic varices on obstetric ultrasonography may allow for treatment before delivery, decreasing the risk of serious maternal morbidity or mortality. Abstract : Abdominal wall varices were identified on obstetric ultrasonography in a patient with liver cirrhosis and portal hypertension, allowing for variceal treatment before delivery.